Pilot study to evaluate usability and acceptability of the "Animated Alcohol Assessment Tool" in Russian primary healthcare - Wiemker, Veronika; Bunova, Anna; Neufeld, Maria; Gornyi, Boris; Yurasova, Elena; Konigorski, Stefan; Kalinina, Anna; Kontsevaya, Anna; Ferreira-Borges, Carina; Probst, Charlotte (Digital health, 2022)
Background and aimsAccurate and user-friendly assessment tools quantifying alcohol consumption are a prerequisite to effective prevention and treatment programmes, including Screening and Brief Intervention. Digital tools offer new potential in this field. We developed the ?Animated Alcohol Assessment Tool? (AAA-Tool), a mobile app providing an interactive version of the World Health Organization's Alcohol Use Disorders Identification Test (AUDIT) that facilitates the description of individual alcohol consumption via culturally informed animation features. This pilot study evaluated the Russia-specific version of the Animated Alcohol Assessment Tool with regard to (1) its usability and acceptability in a primary healthcare setting, (2) the plausibility of its alcohol consumption assessment results and (3) the adequacy of its Russia-specific vessel and beverage selection.MethodsConvenience samples of 55 patients (47% female) and 15 healthcare practitioners (80% female) in 2 Russian primary healthcare facilities self-administered the Animated Alcohol Assessment Tool and rated their experience on the Mobile Application Rating Scale ? User Version. Usage data was automatically collected during app usage, and additional feedback on regional content was elicited in semi-structured interviews.ResultsOn average, patients completed the Animated Alcohol Assessment Tool in 6:38?min (SD?=?2.49, range?=?3.00?17.16). User satisfaction was good, with all subscale Mobile Application Rating Scale ? User Version scores averaging >3 out of 5 points. A majority of patients (53%) and practitioners (93%) would recommend the tool to ?many people? or ?everyone?. Assessed alcohol consumption was plausible, with a low number (14%) of logically impossible entries. Most patients reported the Animated Alcohol Assessment Tool to reflect all vessels (78%) and all beverages (71%) they typically used.ConclusionHigh acceptability ratings by patients and healthcare practitioners, acceptable completion time, plausible alcohol usage assessment results and perceived adequacy of region-specific content underline the Animated Alcohol Assessment Tool's potential to provide a novel approach to alcohol assessment in primary healthcare. After its validation, the Animated Alcohol Assessment Tool might contribute to reducing alcohol-related harm by facilitating Screening and Brief Intervention implementation in Russia and beyond.